2017
DOI: 10.7870/cjcmh-2017-009
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Service Providers’ Perceptions of Barriers and Support Gaps in Housing and Mental Health

Abstract: People experiencing mental illness and homelessness face numerous barriers to becoming housed. Service providers who work with this population also encounter challenges to meeting service users' needs, yet their perspectives have been only minimally studied. Using survey data from a pan-Canadian study, this article explores the barriers and facilitators to fostering lasting change in housing and mental health according to 96 housing providers and 186 community-based mental health service providers. Findings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Immigrant service providers in Canada take a leading role in providing immigrant resettlement services and support for social, economic, and cultural integration into host societies (Kerman et al . ; Maximova & Krahn ). Alberta is a Canadian province with one of the fastest growing populations of foreign‐born nationals; in 2013 and 2014 the proportion of immigrants preparing to settle in Alberta was 14.1% and 16.3%, respectively (Statistics Canada ).…”
Section: Introductionmentioning
confidence: 99%
“…Immigrant service providers in Canada take a leading role in providing immigrant resettlement services and support for social, economic, and cultural integration into host societies (Kerman et al . ; Maximova & Krahn ). Alberta is a Canadian province with one of the fastest growing populations of foreign‐born nationals; in 2013 and 2014 the proportion of immigrants preparing to settle in Alberta was 14.1% and 16.3%, respectively (Statistics Canada ).…”
Section: Introductionmentioning
confidence: 99%
“…While the structure and framing of models of interventions presented in the evidence were varied, common components were linked to the effective provision of support to populations with complex support needs. Collaborative interagency models were defined as partnerships with shared understanding and commitment (Davidson et al, 2014;Gardiner et al, 2017;Kerman et al, 2017). These models typically involved frequent multidisciplinary and multiagency meetings (Ahmed et al, 2016;Campbell et al, 2017;Henning, 2016) or multiagency learning groups that encouraged practitioners to critically reflect on collaboration with partner agencies and exchange professional expertise .…”
Section: Service Levelmentioning
confidence: 99%
“…Interagency collaboration was further enhanced by secure information-sharing systems (Barbabella et al, 2017; Centre for Disability Research and Policy, University of Sydney CDRP and Young People in Nursing Homes National Alliance YPINHNA (2014); Bruns et al, 2015;Morton, 2017), shared practice guidelines and formal protocols (Duffy et al, 2016;Mason et al, 2018;McIntyre et al, 2017), streamlining of administrative processes (Davidson et al, 2014;McKinnon et al, 2016) and allowing sufficient time to collaborate and for team-building (Keesler, 2014;Lee et al, 2013)-all of which required adequate funding (Kerman et al, 2017;Landsdell, 2018;Till et al, 2015). Co-location of services to provide a single point of access and a gateway to a variety of services (Dooris et al, 2013;Dyer and Briddle, 2016;Hardwick, 2015;Whiteford et al, 2013) was identified as effective in facilitating improved information sharing between service users and services and between services and partner agencies (Petch et al, 2013).…”
Section: Service Levelmentioning
confidence: 99%
“…C'est ce que laisse croire un sondage pancanadien où des intervenants du domaine insistent sur l'importance des relations de collaboration et de partenariats pour faciliter la réalisation de leur travail (Kerman et coll. ). De plus, des dimensions de ce tissage de relations peu formalisées et souvent personnalisées apparaissent aussi à l’œuvre dans d'autres villes comme l'indiquent des recherches récentes réalisées à Toronto (LeMoine ), à Washington (Simpson ), à Paris (Cefaï ) ou encore dans différentes municipalités de l’État de Victoria en Australie (Grace, Coventry, et Batterham ).…”
Section: Analyseunclassified